Representasi Pesan Moral dalam Iklan Telkomsel Siaga Edisi Ramadhan #BersamaKitaBerkah - Denny Yustisia Asnadi Putra; Ertika Nanda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Advertisements are a means of communication used by communicators, in this case, producers, or companies, to convey informationabout services or goods, primarily to their customers or consumers. Advertisements are not only a means of promotion but can also serve as a medium for delivering messages. One type of message that can be conveyed in advertisements is the representation of moral messages. This research aims to analyze the moral messages contained in the Telkomsel Siaga Ramadhan Edition #BersamaKitaBerkah advertisement. This research uses a qualitative method with a critical paradigm and a descriptive approach. Data collection techniques include observation and documentation. The theory used is Roland Barthes’ semiotics theory, which analyzes the denotative, connotative, and mythical meanings in the Telkomsel Siaga Ramadhan Edition #BersamaKitaBerkah advertisement. The results of this research show that the denotative and connotative meanings in each scene presented are closely related to everyday life. They remind us to always respect our mothers and appreciate their hard work, dedication, and efforts in raising us. The myth created is that a child should be able to repay the kindness of a mother who has worked hard to support and finance the child. The conclusion is that Telkomsel does not just create advertisements as commercial ads aimed at gaining profit but strives to present works whose story content contain positive moral messages that can be taken as lessons for Telkomsel provider users.